Hydrophobic antifouling polyurethane nanofiber membrane and preparation method thereof

By connecting fluorine -containing silicane plywood on the nano -fiber membrane, the problem of pollutants adhesion caused by hydrophilicity of nano -fiber membrane, and achieved the effect of improving hydrophobic and anti -pollution.

CN119352293AInactive Publication Date: 2025-01-24NINGBO LANGDI TEXTILE TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411897032.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The nanofiber membrane has strong hydrophilicity, which causes pollutants to easily adhere and affect their durability.

Method used

By impregnating the composite nanofiber membrane on the treatment liquid containing fluorite -containing sirriiner coupling agents, the branch fluorine silicon can be applied on the surface of the nano -fiber membrane to improve its hydrophobicity.

Benefits of technology

The hydrophobic and antifouling properties of the nanofiber membrane are improved, reducing the adhesion of dirt and extending its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352293A_ABST
    Figure CN119352293A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrophobic antifouling polyurethane nanofiber membrane and a preparation method thereof, and belongs to the field of membranes. The hydrophobic antifouling polyurethane nanofiber membrane is formed by dipping a composite nanofiber membrane in a treating fluid, and the composite nanofiber membrane is prepared from the following raw materials in parts by weight: 10-15 parts of polyurethane; 3-5 parts of an acrylamide / hydroxy acrylate copolymer; 80-90 parts of a first solvent; the treating fluid comprises a fluorine-containing silane coupling agent; the acrylamide / hydroxyl acrylate copolymer is prepared from an acrylamide monomer, a hydroxyl acrylate monomer, an initiator and a second solvent, wherein the molar ratio of the acrylamide monomer to the hydroxyl acrylate monomer is 1: (0.25-0.35). The preparation method has the effect of improving the hydrophobic antifouling property of the nanofiber membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of thin films, and in particular to a hydrophobic and antifouling polyurethane nanofiber membrane and a preparation method thereof. Background Art

[0002] Nanofiber membrane is a thin film material composed of nanometer-scale fibers, whose fiber diameter is usually between 1 and 100 nanometers. This material has great application potential in many fields due to its excellent microstructure and performance. The characteristics of nanofiber membrane include high specific surface area, high porosity, high surface roughness and high orientation, so it can be used in water treatment, air purification, tissue engineering, smart wearable devices and sensors, etc., and has significant application value.

[0003] There are various techniques for preparing nanofiber membranes, among which electrospinning is widely favored due to its ease of operation. This method applies high voltage to a polymer solution to cause polymer molecules to deposit on a substrate in the form of nanoscale fibers to form a nanofiber membrane.

[0004] However, due to the high specific surface area and porosity of the nanofiber membrane, the general nanofiber membrane is more hydrophilic, and pollutants are more easily adhered after contact, affecting the durability of the nanofiber membrane. Summary of the invention

[0005] In order to improve the hydrophobic and antifouling properties of a nanofiber membrane, the present application provides a hydrophobic and antifouling polyurethane nanofiber membrane and a preparation method thereof.

[0006] In the first aspect, the hydrophobic and antifouling polyurethane nanofiber membrane provided in the present application adopts the following technical solution: The hydrophobic and antifouling polyurethane nanofiber membrane is formed by impregnating a composite nanofiber membrane with a treatment liquid, wherein the composite nanofiber membrane is prepared from the following raw materials in parts by weight: Polyurethane 10-15 parts; 3-5 parts of acrylamide / hydroxy acrylate copolymer; 80-90 parts of the first solvent; The treatment liquid contains a fluorine-containing silane coupling agent; The acrylamide / hydroxy acrylate copolymer is prepared from acrylamide monomer, hydroxy acrylate monomer, an initiator and a second solvent, wherein the molar ratio of the acrylamide monomer to the hydroxy acrylate monomer is 1:(0.25-0.35).

[0007] By adopting the above technical scheme, the composite nanofiber membrane is immersed in the treatment liquid, so that the fluorine-containing silane coupling agent is grafted into the pores of the composite nanofiber membrane, thereby introducing fluorosilicone functional groups into the surface of the nanofiber membrane, and utilizing the hydrophobic properties of the fluorosilicone functional groups to improve the hydrophobicity of the nanofiber membrane surface, reduce the adhesion of dirt, and thus improve the anti-fouling performance.

[0008] The composite nanofiber membrane is based on polyurethane as the main resin and is composited with acrylamide / hydroxy acrylate copolymer. Hydroxyl acrylate provides grafting reaction sites for fluorinated silane coupling agents. The acrylamide / hydroxy acrylate copolymer chain segments and polyurethane form an entangled composite structure under the action of hydrogen bonds, which improves the structural stability of the nanofiber membrane and promotes the uniform combination of the hydroxy acrylate part with the polyurethane, further improving the grafting rate and grafting uniformity of the fluorinated silane coupling agent, and improving the hydrophobic and antifouling effect.

[0009] The polymerization ratio of acrylamide monomer to hydroxy acrylate monomer is controlled so that the chain segment characteristics of the copolymer and the polyurethane chain segment cooperate with each other, thereby improving the overall toughness of the composite nanofiber membrane.

[0010] Optionally, the acrylamide monomer includes one or more of acrylamide, methacrylamide and N-isopropylacrylamide; the hydroxy acrylate monomer includes one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate and hydroxypropyl methacrylate.

[0011] Optionally, the treatment liquid contains a fluorine-containing silane coupling agent and a third solvent, and the mass fraction of the fluorine-containing silane coupling agent in the treatment liquid is 10-20%.

[0012] By adopting the above technical solution, the mass fraction of the fluorinated silane coupling agent in the treatment liquid will affect the process and rate of grafting, so an appropriate mass fraction can improve the grafting effect, thereby improving the hydrophobic and antifouling effect of the polyurethane nanofiber membrane.

[0013] Optionally, the fluorine-containing silane coupling agent includes one or more of nonafluorohexyltrimethoxysilane, dodecafluoroheptylpropyltrimethoxysilane and tridecafluorooctyltrimethoxysilane.

[0014] By adopting the above technical solution, the above fluorinated silane coupling agent has a moderate chain length and a high interfacial bonding ability with the acrylamide / hydroxy acrylate copolymer, so the hydrophobic and antifouling effect of the polyurethane nanofiber membrane can be further improved. If a fluorinated silane coupling agent with a shorter chain segment is selected, the fluorine functional group content is insufficient and the hydrophobic effect is poor. If a fluorinated silane coupling agent with an overly long chain segment is selected, grafting is difficult and the hydrophobicity after grafting is insufficient to provide an antifouling effect.

[0015] Optionally, the acrylamide / hydroxy acrylate copolymer is prepared from N-isopropyl acrylamide and hydroxypropyl acrylate, and the fluorine-containing silane coupling agent is tridecafluorooctyltrimethoxysilane.

[0016] By adopting the above technical scheme, the interface characteristics of the acrylamide / hydroxyacrylate copolymer prepared from the above monomers are compatible with tridecafluorooctyltrimethoxysilane, which can further improve the uniformity and stability of grafting, thereby improving the toughness and filtration efficiency of the polyurethane nanocellulose membrane.

[0017] Optionally, the initiator includes one or both of potassium persulfate and ammonium persulfate.

[0018] Optionally, the first solvent includes one or more of dimethylformamide, dimethylacetamide and dimethylpropionamide.

[0019] Optionally, the second solvent is water.

[0020] Optionally, the third solvent is one or both of methanol and ethanol.

[0021] Optionally, the polyurethane is a thermoplastic polyether polyurethane.

[0022] In the second aspect, the preparation method of the hydrophobic and antifouling polyurethane nanofiber membrane provided in the present application adopts the following technical scheme: Optionally, the method for preparing the hydrophobic and antifouling polyurethane nanofiber membrane comprises the following steps: The polyurethane and acrylamide / hydroxyacrylate copolymer are dissolved in a first solvent to prepare a spinning solution, and an electrostatic spinning device is used for spinning to obtain a composite nanofiber membrane; The composite nanofiber membrane is immersed in the treatment liquid for 18 to 30 hours at a temperature of 45 to 55° C. After the immersion, it is washed and dried to obtain a hydrophobic and antifouling polyurethane nanofiber membrane.

[0023] By adopting the above technical scheme, polyurethane and acrylamide / hydroxyacrylate copolymer are first compounded to form a composite nanofiber membrane, and then a fluorine-containing silane coupling agent is grafted by immersion in a treatment liquid, so that fluorine functional groups can be introduced into the surface of the polyurethane nanofiber membrane to form a hydrophobic and antifouling effect, and reduce the impact on the mechanical properties of the polyurethane nanofiber membrane, thereby broadening the application scenarios of the polyurethane nanofiber membrane.

[0024] Optionally, the preparation method of the acrylamide / hydroxy acrylate copolymer comprises the following steps: The acrylamide monomer and hydroxy acrylate are stirred and mixed evenly in the second solvent, the temperature is raised to 50-60° C., the initiator is added in batches, and the reaction is continued for 2-3 hours after the initiator is added. After the reaction is completed, it is filtered, washed and dried to obtain an acrylamide / hydroxy acrylate copolymer.

[0025] Optionally, the spinning speed is 1-1.5 mL / h, and the distance between the spinneret and the receiving device is 13-17 cm.

[0026] In summary, this application has the following beneficial effects: 1. The nanofiber membrane of the present application is treated by immersion in a treatment liquid, so that the fluorine-containing silane coupling agent is grafted into the pores of the composite nanofiber membrane, thereby introducing fluorine-silicon functional groups into the surface of the nanofiber membrane, and utilizing the hydrophobic properties of the fluorine-silicon functional groups to improve the hydrophobicity of the surface of the nanofiber membrane, reduce the adhesion of dirt, and thus improve the anti-fouling performance; 2. The composite nanofiber membrane is based on polyurethane as the main resin and is composited with acrylamide / hydroxy acrylate copolymer. Hydroxyl acrylate provides grafting reaction sites for fluorinated silane coupling agents. The acrylamide / hydroxy acrylate copolymer chain segments and polyurethane form an entangled composite structure under the action of hydrogen bonds, which improves the structural stability of the nanofiber membrane and promotes the uniform combination of the hydroxy acrylate part with the polyurethane, further improving the grafting rate and uniformity of the fluorinated silane coupling agent, and improving the hydrophobic and antifouling effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a SEM image of the polyurethane nanofiber membrane of Example 3 of the present application. DETAILED DESCRIPTION

[0028] The following is combined with Figure 1 This application is described in further detail.

[0029] Preparation Example 1 The preparation method of acrylamide / hydroxy acrylate copolymer comprises the following steps: Weigh 355 g of acrylamide and 162.5 g of hydroxyethyl methacrylate, stir and mix acrylamide and hydroxyethyl methacrylate evenly in 5 L of water, heat to 50°C, add 10 g of potassium persulfate in four equal batches within 1 hour, continue to react for 3 hours after the addition of potassium persulfate, filter after the reaction is completed, wash with water, and dry in an oven at 40°C for 1 hour to obtain an acrylamide / hydroxy acrylate copolymer.

[0030] Preparation Example 2 The preparation method of acrylamide / hydroxy acrylate copolymer comprises the following steps: Weigh 355 g of acrylamide and 227.5 g of hydroxyethyl methacrylate, stir and mix acrylamide and hydroxyethyl methacrylate evenly in 5 L of water, heat to 60°C, add 10 g of potassium persulfate in four equal batches within 1 hour, continue to react for 2 hours after the addition of potassium persulfate, filter after the reaction is completed, wash with water, and dry in an oven at 40°C for 1 hour to obtain an acrylamide / hydroxy acrylate copolymer.

[0031] Preparation Example 3 Preparation method of acrylamide / hydroxy acrylate copolymer. The difference between this preparation example and preparation example 1 is that the original 227.5 g of hydroxyethyl methacrylate is replaced by 227.5 g of hydroxypropyl acrylate.

[0032] Preparation Example 4 Preparation method of acrylamide / hydroxy acrylate copolymer. The difference between this preparation example and preparation example 1 is that the original 355g of acrylamide is replaced by 565g of isopropyl acrylamide, and the original 162.5g of hydroxyethyl methacrylate is replaced by 145g of hydroxyethyl acrylate.

[0033] Preparation Example 5 Preparation method of acrylamide / hydroxy acrylate copolymer. The difference between this preparation example and preparation example 1 is that the original 355g of acrylamide is replaced by 565g of isopropyl acrylamide, and the original 162.5g of hydroxyethyl methacrylate is replaced by 162.5g of hydroxypropyl acrylate.

[0034] Comparative Preparation Example 1 The preparation method of hydroxy acrylate polymer comprises the following steps: Weigh 812.5 g of hydroxyethyl methacrylate, disperse it in 5 L of water, heat it to 50°C, add 10 g of potassium persulfate in four equal batches within 1 hour, continue the reaction for 3 hours after the addition of potassium persulfate, filter it after the reaction is completed, wash it with water, and dry it in an oven at 40°C for 1 hour to obtain a hydroxy acrylate polymer.

[0035] Comparative Preparation Example 2 The preparation method of acrylic acid / hydroxy acrylate copolymer comprises the following steps: Weigh 360 g of acrylic acid and 162.5 g of hydroxyethyl methacrylate, stir and mix the acrylic acid and hydroxyethyl methacrylate evenly in 5 L of water, heat to 50° C., add 10 g of potassium persulfate in four equal batches within 1 hour, continue to react for 3 hours after the addition of potassium persulfate, add sodium hydroxide solution after the reaction is completed to adjust the pH to neutral, filter, wash with water, and dry in an oven at 40° C. for 1 hour to obtain an acrylic acid / hydroxy acrylate copolymer.

[0036] Example 1

[0037] The method for preparing a hydrophobic and antifouling polyurethane nanofiber membrane comprises the following steps: Weigh 1 kg of polyurethane and 0.3 kg of acrylamide / hydroxy acrylate copolymer, wherein the polyurethane is a thermoplastic polyether polyurethane, has a hard segment content of 40%, and an isocyanate index R value of 0.99; the acrylamide / hydroxy acrylate copolymer is prepared by Preparation Example 1. The polyurethane and acrylamide / hydroxy acrylate copolymer are dissolved in 8 kg of dimethylformamide to prepare a spinning solution, and an electrospinning device is used for spinning at a spinning speed of 1 mL / h. The distance between the spinneret and the receiving device is 13 cm to obtain a composite nanofiber membrane.

[0038] The composite nanofiber membrane is completely immersed in a treatment solution composed of tridecafluorooctyltrimethoxysilane and ethanol. The mass fraction of tridecafluorooctyltrimethoxysilane in the treatment solution is 10%. The immersion time is 30 hours and the immersion temperature is 45°C. After the immersion, it is washed with ethanol and dried in an oven at 45°C for 1 hour to obtain a hydrophobic and antifouling polyurethane nanofiber membrane.

[0039] Example 2

[0040] The method for preparing a hydrophobic and antifouling polyurethane nanofiber membrane comprises the following steps: Weigh 1.5 kg of polyurethane and 0.5 kg of acrylamide / hydroxy acrylate copolymer, wherein the polyurethane is a thermoplastic polyether polyurethane, with a hard segment content of 40% and an isocyanate index R value of 0.99; the acrylamide / hydroxy acrylate copolymer is prepared by Preparation Example 2. The polyurethane and acrylamide / hydroxy acrylate copolymer are dissolved in 9 kg of dimethylformamide to prepare a spinning solution, and an electrostatic spinning device is used for spinning at a spinning speed of 1.5 mL / h. The distance between the spinneret and the receiving device is 17 cm to obtain a composite nanofiber membrane.

[0041] The composite nanofiber membrane was immersed in a treatment liquid composed of tridecafluorooctyltrimethoxysilane and ethanol. The mass fraction of tridecafluorooctyltrimethoxysilane in the treatment liquid was 20%. The immersion time was 18 hours and the immersion temperature was 45°C. After the immersion, it was washed with ethanol and dried in an oven at 45°C for 1 hour to obtain a hydrophobic and antifouling polyurethane nanofiber membrane.

[0042] Example 3

[0043] The method for preparing a hydrophobic and antifouling polyurethane nanofiber membrane comprises the following steps: Weigh 1.2 kg of polyurethane and 0.4 kg of acrylamide / hydroxy acrylate copolymer, wherein the polyurethane is a thermoplastic polyether polyurethane, has a hard segment content of 40%, and an isocyanate index R value of 0.99; the acrylamide / hydroxy acrylate copolymer is prepared by Preparation Example 1. The polyurethane and acrylamide / hydroxy acrylate copolymer are dissolved in 8.5 kg of dimethylformamide to prepare a spinning solution, and an electrospinning device is used for spinning at a spinning speed of 1 mL / h. The distance between the spinneret and the receiving device is 13 cm to obtain a composite nanofiber membrane.

[0044] The composite nanofiber membrane was immersed in a treatment liquid composed of tridecafluorooctyltrimethoxysilane and ethanol. The mass fraction of tridecafluorooctyltrimethoxysilane in the treatment liquid was 15%. The immersion time was 24 hours and the immersion temperature was 50°C. After the immersion, it was washed with ethanol and dried in an oven at 45°C for 1 hour to obtain a hydrophobic and antifouling polyurethane nanofiber membrane.

[0045] Example 4

[0046] The method for preparing a hydrophobic and antifouling polyurethane nanofiber membrane is different from Example 3 in that the acrylamide / hydroxy acrylate copolymer of this example is prepared by Preparation Example 3.

[0047] Example 5

[0048] The method for preparing a hydrophobic and antifouling polyurethane nanofiber membrane is different from Example 3 in that the acrylamide / hydroxy acrylate copolymer of this example is prepared by Preparation Example 4.

[0049] Example 6

[0050] The method for preparing a hydrophobic and antifouling polyurethane nanofiber membrane is different from Example 3 in that the acrylamide / hydroxy acrylate copolymer of this example is prepared by Preparation Example 5.

[0051] Example 7

[0052] Preparation method of hydrophobic antifouling polyurethane nanofiber membrane, the difference between this embodiment and embodiment 3 is that the acrylamide / hydroxy acrylate copolymer of this embodiment is prepared by preparation example 5. In addition, the tridecafluorooctyltrimethoxysilane in the treatment liquid is replaced with nonafluorohexyltrimethoxysilane, and the mass fraction of nonafluorohexyltrimethoxysilane in the treatment liquid is 15%.

[0053] Comparative Example 1 The method for preparing a nanofiber membrane comprises the following steps: 1.6 kg of polyurethane was weighed, wherein the polyurethane was a thermoplastic polyether polyurethane, with a hard segment content of 40% and an isocyanate index R value of 0.99. The polyurethane was dissolved in 8.5 kg of dimethylformamide to prepare a spinning solution, and an electrospinning device was used for spinning at a spinning speed of 1 mL / h. The distance between the spinneret and the receiving device was 13 cm to obtain a nanofiber membrane.

[0054] Comparative Example 2 The method for preparing a hydrophobic and antifouling polyurethane nanofiber membrane comprises the following steps: 1.6 kg of polyurethane was weighed, wherein the polyurethane was a thermoplastic polyether polyurethane, with a hard segment content of 40% and an isocyanate index R value of 0.99. The polyurethane was dissolved in 8.5 kg of dimethylformamide to prepare a spinning solution, and an electrospinning device was used for spinning at a spinning speed of 1 mL / h. The distance between the spinneret and the receiving device was 13 cm to obtain a nanofiber membrane.

[0055] The nanofiber membrane was immersed in a treatment liquid composed of tridecafluorooctyltrimethoxysilane and ethanol. The mass fraction of tridecafluorooctyltrimethoxysilane in the treatment liquid was 15%. The immersion time was 24 hours and the immersion temperature was 50°C. After the immersion, it was washed with ethanol and dried in an oven at 45°C for 1 hour to obtain a hydrophobic and antifouling polyurethane nanofiber membrane.

[0056] Comparative Example 3 The method for preparing a hydrophobic and antifouling polyurethane nanofiber membrane is different from Example 3 in that in this comparative example, 0.4 kg of acrylamide / hydroxy acrylate copolymer is replaced by 0.4 kg of hydroxy acrylate polymer, and the hydroxy acrylate polymer is prepared by Comparative Preparation Example 1.

[0057] Comparative Example 4 The method for preparing a hydrophobic and antifouling polyurethane nanofiber membrane is different from Example 3 in that in this comparative example, 0.4 kg of acrylamide / hydroxy acrylate copolymer is replaced by 0.4 kg of acrylic acid / hydroxy acrylate copolymer, and the acrylic acid / hydroxy acrylate copolymer is prepared by Comparative Preparation Example 2.

[0058] Effect test Hydrophobic effect: The water contact angle test was performed on the nanofiber membranes prepared in various embodiments and comparative examples using a contact angle tester, with a water drop volume of 3 μL. The results are shown in Table 1.

[0059] Antifouling effect: Take the nanofiber membranes prepared in various embodiments and comparative examples as samples, apply a pollutant on the surface of the sample to form a pollution spot, the pollutant is engine oil, and the pollution spot is a 30mm square. Dry at room temperature for 24 hours after application, and then use a white cotton cloth soaked in warm water to wipe the pollution spot evenly and forcefully. Wipe it 100 times in total, one round trip is counted as 1 time, and observe whether the pollution spot is wiped off after every 10 wipes. Record the number of wiping times when the pollution spot is wiped off. If the pollution spot cannot be wiped off, it will be recorded as >100. The results are shown in Table 1.

[0060] Mechanical properties: The breaking strain test of the nanofiber membranes prepared in various embodiments and comparative examples was carried out using an electronic universal testing machine at a tensile speed of 0.8 mm / min. The results are shown in Table 2.

[0061] Filtration performance: The filtration efficiency of the nanofiber membranes prepared in each embodiment and comparative example was tested using an automatic filter material tester. The test aerosol was NaCl aerosol particles with a flow rate of 32 L / min. The results are shown in Table 2.

[0062]

[0063]

[0064] From the analysis of Table 1, the polyurethane nanofiber membrane prepared in the embodiment of the present application has a large water contact angle and can completely wipe off the pollution stain within 60 times, so it has good hydrophobic and anti-fouling effects.

[0065] Comparative Example 1 is a traditional polyurethane nanofiber membrane. It can be seen that the polyurethane nanofiber membrane of Example 1 is superior to that of Comparative Example 1 in terms of hydrophobicity and antifouling. Combined with Comparative Example 2, it can be seen that Example 1 can greatly improve the hydrophobicity and antifouling effects in the form of a composite film of polyurethane and acrylamide / hydroxy acrylate copolymer. Further combined with Comparative Example 3 and Comparative Example 4, it can be seen that the hydrophobicity and antifouling synergistic effect of acrylamide and hydroxy acrylate copolymerization.

[0066] From the analysis of Table 2, the polyurethane nanofibers prepared in the examples of the present application have good fracture strain maintenance and high filtration efficiency, and therefore have good toughness and filtration performance.

[0067] In combination with Example 4 to Example 7, it can be seen that different acrylamide monomers, different hydroxyacrylate monomers and different fluorinated silane coupling agents have a significant effect on the toughness and filtration performance of the polyurethane nanofiber membrane. When N-isopropylacrylamide, hydroxypropyl acrylate and tridecafluorooctyltrimethoxysilane are specifically selected for combination, the toughness and filtration performance of the polyurethane nanofiber membrane are improved.

[0068] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A hydrophobic and antifouling polyurethane nanofiber membrane, characterized in that: The composite nanofiber membrane is impregnated with a treatment liquid, and the composite nanofiber membrane is prepared from the following raw materials in parts by weight: Polyurethane 10-15 parts; 3-5 parts of acrylamide / hydroxy acrylate copolymer; 80-90 parts of the first solvent; The treatment liquid contains a fluorine-containing silane coupling agent; The acrylamide / hydroxy acrylate copolymer is prepared from acrylamide monomer, hydroxy acrylate monomer, an initiator and a second solvent, wherein the molar ratio of the acrylamide monomer to the hydroxy acrylate monomer is 1:(0.25-0.35).

2. The hydrophobic and antifouling polyurethane nanofiber membrane according to claim 1, characterized in that: The acrylamide monomer includes one or more of acrylamide, methacrylamide and N-isopropyl acrylamide; the hydroxy acrylate monomer includes one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate and hydroxypropyl methacrylate.

3. The hydrophobic and antifouling polyurethane nanofiber membrane according to claim 1, characterized in that: The treatment liquid contains a fluorine-containing silane coupling agent and a third solvent, and the mass fraction of the fluorine-containing silane coupling agent in the treatment liquid is 10-20%.

4. The hydrophobic and antifouling polyurethane nanofiber membrane according to claim 1, characterized in that: The fluorine-containing silane coupling agent includes one or more of nonafluorohexyltrimethoxysilane, dodecafluoroheptylpropyltrimethoxysilane and tridecafluorooctyltrimethoxysilane.

5. The hydrophobic and antifouling polyurethane nanofiber membrane according to claim 1, characterized in that: The acrylamide / hydroxy acrylate copolymer is prepared from N-isopropyl acrylamide and hydroxypropyl acrylate, and the fluorine-containing silane coupling agent is tridecafluorooctyl trimethoxysilane.

6. The hydrophobic and antifouling polyurethane nanofiber membrane according to any one of claims 1 to 5, characterized in that: The polyurethane is thermoplastic polyether polyurethane.

7. A method for preparing the hydrophobic and antifouling polyurethane nanofiber membrane according to any one of claims 1 to 6, characterized in that: The following steps are involved: The polyurethane and acrylamide / hydroxyacrylate copolymer are dissolved in a first solvent to prepare a spinning solution, and an electrostatic spinning device is used for spinning to obtain a composite nanofiber membrane; The composite nanofiber membrane is immersed in the treatment liquid for 18 to 30 hours at a temperature of 45 to 55° C. After the immersion, it is washed and dried to obtain a hydrophobic and antifouling polyurethane nanofiber membrane.

8. The method for preparing the hydrophobic and antifouling polyurethane nanofiber membrane according to claim 7, characterized in that: The preparation method of the acrylamide / hydroxy acrylate copolymer comprises the following steps: The acrylamide monomer and hydroxy acrylate are stirred and mixed evenly in the second solvent, the temperature is raised to 50-60° C., the initiator is added in batches, and the reaction is continued for 2-3 hours after the initiator is added. After the reaction is completed, it is filtered, washed and dried to obtain an acrylamide / hydroxy acrylate copolymer.

9. The method for preparing the hydrophobic and antifouling polyurethane nanofiber membrane according to claim 7, characterized in that: The spinning speed is 1~1.5mL / h, and the distance between the spinneret and the receiving device is 13~17 cm.

Citation Information

Patent Citations

  • Temperature-sensitive type finishing agent as well as preparation method and applications thereof

    CN101994253A

  • Preparation method of temperature-responsive type nanofiber dressing

    CN112695411A

  • Antifogging coating as well as preparation method and application thereof

    CN114231160A

  • Hydrophobic antibacterial antifouling polyurethane nanofiber membrane and preparation method thereof

    CN117364343A

  • Manufacturing method of super-hydrophobic PMMA (polymethyl methacrylate) material and super-hydrophobic PMMA material

    CN117510958A